Potensi Ekologis Sumber Daya Laut: Pemberdayaan Nelayan Berbasis Tafsir Ilmi Untuk Konservasi di Daerah Karangjaya: Penelitian - Siti Nur Azizah; Altaf Abdurahman; Lulu Nurul Khasanah; Andi Rosa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The ecological potential of marine resources in the coastal area of ​​Karangjaya can be seen from the various riches and abundance of the components living far from the big city population, gradually. Karangjaya has multiple materials that can be used as tools to survive, considering that Karangjaya is very strategic in searching for fish, coral, and sea sand. However, the problem is that Karangjaya still cannot cultivate the results of its livelihood. The most striking issues are the challenges in the management of its problems. Scientific interpretation is present in studying materialistic objects and components of an item to explore messages related to the ecology of Karangjaya empowerment in increasing local wisdom and planting reason in cultivating it, in the object of scientific interpretation based on the object of marine study. This study was conducted to find out what shortcomings are not yet known to the Karangjaya population from the aspect of wisdom and cultivation, where scientific interpretation that discusses maritime can help develop local wisdom and can cultivate the results of its livelihood.